Kingdom of the Netherlands - Netherlands : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This Selected Issues paper examines the long-term issues with pension expenditures in the Netherlands. The paper highlights that the public pension for a single person is equal to 70 percent of the (statutory) minimum wage. The minimum wage and public pensions thus move in lock-step; they are both by law indexed to contract wages in the private sector. This paper examines the structural policies of the Netherlands. Real wages and employment growth are also analyzed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet